Effect of Dietary Supplementation of Arginine, Tryptophan, and Taurine on Productive Performance, Egg Quality, and Health Status of Laying Hens Raised Under Heat Stress Conditions - C. H. Kwon; J. H. Nam; G. P. Han; D. Y. Kim; D. Y. Kil (Tropical Animal Science Journal, 2023)
The objective of this experiment was to investigate the effect of dietary supplementation of arginine (Arg), tryptophan (Trp), and taurine (Tau) on productive performance, egg quality, liver visual characteristics, antioxidant status, immune response, and stress indicator of laying hens raised under heat stress conditions. A total of two hundred eighty 47-wk-old Hy-Line Brown laying hens were randomly allotted to 1 of 4 dietary treatments with 7 replicates consisting of 10 cages per replicate. A basal diet (BD) was prepared to meet or exceed nutrient requirement estimates. Two additional diets were formulated to increase either digestible Arg or Trp by 50% greater than the BD. Finally, one more diet was prepared by adding 0.5% Tau to the BD. The experimental diets were fed to hens on an ad libitum basis for 8 wk. Average room temperature and relative humidity were maintained at 30.7±1.41°C and 72.5±11.61%, respectively. Results indicated that laying hens in Arg and Trp treatments tended (p= 0.06) to have a higher egg yolk color (Roche color fan) than those in the Tau treatment. Likewise, there was a tendency (p= 0.05) for a lower liver color score in the Tau treatment than Arg and Trp treatments. In conclusion, dietary supplementation of Arg, Trp, and Tau at the current levels (0.37% SID Arg, 0.075% SID Trp, and 0.5% Tau) in diets has no positive effects on productive performance, egg quality, liver visual characteristics, antioxidant status, immune response, and stress indicators of laying hens raised under the current heat stress conditions.